Transient swelling behaviour of dual stimuli sensitive nanocomposite hydrogels. (16th March 2020) - Mousazadeh, Saeed; Kokabi, Mehrdad
Abstract: Smart nanocomposite hydrogels can undergo large deformation under external stimuli. Several coupled physical processes simultaneously affect the transient swelling behaviour of pH and temperature-sensitive hydrogels. Besides, the hydrogel properties change in response to the external stimuli in the presence of nanoparticles, which affect its transient deformation and swelling behaviour. This work focused on transient swelling modeling of pH and temperature-sensitive polymer/clay nanocomposite hydrogels. The time-dependent processes were considered simultaneously with material properties updating in each time-step during the finite element procedure. A set of experiments was designed to evaluate the numerical solving results in the free and constrained swelling conditions. The results illustrate that the proposed developed model successfully predicts the transient swelling behaviour of pH and temperature-sensitive either for hydrogels or nanocomposite hydrogel counterparts, which can offer a guideline to the abundant usage of these soft materials. Graphical abstract: Image 1 Highlights: The proposed model satisfactorily predicted the transient swelling of smart nanocomposite hydrogels. A new parameter introduced to consider the effect of clay nanolayer in osmotic pressure. Two scenarios of swelling (free and constrained swelling) revealed by numerical simulation. Material properties of sensitive nanocomposite hydrogels changed due to the swelling process.